1974
DOI: 10.1051/forest/19740301
|View full text |Cite
|
Sign up to set email alerts
|

Bilan d'une expérience comparative de provenances de mélèzes à l'âge de 13 ans

Abstract: RÉSUMÉCet article fait le bilan à 13 ans d'une expérience comparative de provenances de mélèze (expé-rience internationale du Pr. SCHOBER) installée en Bretagne.Outre les caractères de vigueur, une attention spéciale a été donnée aux caractères de forme du tronc et de la cime. Les résultats montrent la très grande supériorité de certains hybrides (Larix eurolepis) et l'intérêt de la région de provenances « Sudètes ». Cependant, pour ces provenances, la forme, très variable, mérite d'être améliorée par sélectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Regarding stem straightness, the differences were small and rarely significant. The hybrids were no straighter than the parent species, contrary to what Lacaze and Birot (1974) observed.…”
Section: Performance Of Hybrids Versus Non-hybrid Treescontrasting
confidence: 93%
See 1 more Smart Citation
“…Regarding stem straightness, the differences were small and rarely significant. The hybrids were no straighter than the parent species, contrary to what Lacaze and Birot (1974) observed.…”
Section: Performance Of Hybrids Versus Non-hybrid Treescontrasting
confidence: 93%
“…Not only does hybrid larch (Larix 9 eurolepis Henry) feature good resistance to larch canker (Lachnellula willkommii) (Edwards 1956;Sylvestre et al 1999), it has shown better growth than either parent species in many instances (e.g. Ferrand and Bastien 1985;Pâques 1992;Baltunis et al 1998;Pâques et al 2013) and sometimes has a better form (Lacaze and Birot 1974) and a better survival rate (Miller and Thulin 1967;Zaczek et al 1994). For wood properties, the hybrid is usually intermediate between EL and JL or better than the best parent (Nanson and Sacré 1978;Reck 1980;Bastien and Keller 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of authors have observed a link between crown width and larch vigour (e.g. LACAZE and BIROT, 1974;STIPANICIC, 1984;BALTUNIS and GREENWOOD, 1996). L. decidua or L. kaempferi as mother trees of HL: breeding (≈ 2008 -2013) and testing (≈ 2016 -2035) At present, we don't know if one hybrid type (E x J or J x E) out performs the other in growth rate, because few progenies have been compared and few studies have used the same parent material.…”
Section: Methodsmentioning
confidence: 99%
“…Other examples have been given by Vincent and Fer (1965) and Lacaze and Birot (1974 The greater uniformity of the F 1 generation progeny over the parental progenies has also been recognized as an advantage in favor of hybrids. This was the main conclusion drawn by Lacaze and Birot (1974) (Nilsson, 1959) and with Larix laricina for its presumably good adaptation to wet soils (Ferrand, 1986 (Keiding, 1980;Reck, 1977;Vincent and Machanicek, 1972 Keiding (1980) (Hinkelmann, 1974) or better suited to our purposes, a nested population diallel or factorial mating design such as that used by Park and Gerhold (1986) (Namkoong, 1979;Falconer, Keiding (1968). His results, based on a limited number of crossings between two noninbred European larch parents and a few number of first-generation selfed (S1) parents of Japanese larch, show that nonnegligible supplementary gains (5-10%) and uniformity for total height can be obtained in this manner compared to normal (no selfing) inter-specific crossing.…”
Section: Introductionmentioning
confidence: 95%
“…seed sources from their native range (the Alps) to more lowland areas has not been successful in France. Several provenance tests have shown its poor adaptation, slow growth, and canker susceptibility (Lacaze and Birot, 1974;Ferrand and Bastien, 1985, Schober, 1985 when cultivated at lower elevations. On the other hand, Japanese larch Larix kaempferi (Lamb.)…”
Section: Introductionmentioning
confidence: 99%